Impaired Glymphatic Transport Kinetics Following Induced Acute Ischemic Brain Edema in a Mouse pMCAO Model - Zhang, Jianying; Zhao, Hongchen; Xue, Yang; Liu, Yiqi; Fan, Guohang; Wang, He; Dong, Qiang; Cao, Wenjie (Frontiers in Neurology, 2022)
Background: Cerebral edema forms immediately after blood flow interruption in ischemic stroke, which largely increased the death and disability. The glymphatic pathway is a major regulator of the brain liquid dynamics and homeostasis. The present study aimed to investigate the transport kinetics of the glymphatic system after the appearance of ischemic edema. Methods: In this study, a coated filament was attached to the left MCA of mice to establish a mouse model of permanent middle cerebral artery occlusion (pMCAO) with an intact BBB. The glymphatic function was then quantified using contrast-enhanced MRI (11.7T) by employing an injection of gadobenate dimeglumine (BOPTA-Gd) into the cisterna magna of mice. We then evaluated the expression and polarization of aquaporin-4 as a proxy for the physiological state of the glymphatic system. Results: Our results revealed a positive correlation between the signal intensity in T1W images and the corresponding ADC value in the cortex, striatum, and periventricular zone, suggesting that impaired glymphatic transport kinetics in these regions is correlated to the cytotoxic edema induced by the occlusion of MCA. Furthermore, the increased depolarization of aquaporin-4 in both the parenchyma periventricular space (PVS) and periventricular zone was consistent with glymphatic failure following the induced ischemic edema. Conclusions: Glymphatic transport kinetics were suppressed between the onset of cytotoxic edema and the disruption of the BBB, which correlated with the diminishing ADC values that vary based on edema progression, and is associated with depolarization of aquaporin-4 in both the parenchyma PVSs and periventricular zone.